Influence of salt and temperature in the growth of pathogenic free-living amoebae - Arberas-Jiménez, Iñigo; Rodríguez-Expósito, Rubén L.; Sifaoui, Ines; Chao-Pellicer, Javier; Sancho, Luis; Urruticoechea, Andoni; Piñero, José E.; Lorenzo-Morales, Jacob (Frontiers in Microbiology, 2024)
Free-living amoebae are an extensive group of protistans that can be found in a wide variety of environments. Among them, the Acanthamoeba genus and Naegleria fowleri stand out as two of the most pathogenic amoebae and with a higher number of reported cases. N. fowleri is mainly found in warm freshwater water bodies whereas amoebae of the Acanthamoeba genus are broadly distributed through natural and anthropogenic environments. In this regard, the management and the control of the amoebic populations in swimming pools has become a major public health challenge for institutions. The aim of this work was to evaluate the growth pattern of trophozoites of A. griffini and N. fowleri at different temperatures and salt concentrations. Our results showed that A. griffin resisted a higher concentration of salt than N. fowleri. Moreover, no trophozoites could withstand the salt levels of the sea in in vitro conditions. This work supports the contention that salinity could represent an important and useful tool for the control of the most pathogenic amoebic populations in recreational water bodies.